2002
DOI: 10.1002/1521-4141(200209)32:9<2672::aid-immu2672>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DNA autoreactivity in C4-deficient mice

Abstract: Mice lacking the classical complement component C4 (C4–/–) were evaluated for autoreactivity because classical complement deficiencies are major risk factors for human systemic lupus erythematosus (SLE). Naive, 6‐month‐old C4–/– mice have significantly more IgM anti‐double‐strand DNA antibodies than C4+/+ controls. By 9 months, IgG anti‐dsDNA antibodies are increased and this spontaneous autoreactivity is evident across a mixture of genetic backgrounds. C4+/– heterozygous mice also develop autoantibodies, remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Interestingly, ablation of the C4 gene, located at the peak marker used in the original linkage studies describing Sles1, has been demonstrated to alter negative selection of immature self-reactive B cells in both the double-transgenic hen egg lysosome and the lpr null models (4,50). Furthermore, unlike other complement deficiencies (C1qa, C3, and Cr1/2), the lack of C4 appears less dependent on a mixed 129 ϫ B6 background for the manifestation of some degree of autoimmunity (7). However, serum levels of this complement component are equivalent in young, preautoimmune B6, B6.Sle1 and B6.Sle1 Sles1 mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ablation of the C4 gene, located at the peak marker used in the original linkage studies describing Sles1, has been demonstrated to alter negative selection of immature self-reactive B cells in both the double-transgenic hen egg lysosome and the lpr null models (4,50). Furthermore, unlike other complement deficiencies (C1qa, C3, and Cr1/2), the lack of C4 appears less dependent on a mixed 129 ϫ B6 background for the manifestation of some degree of autoimmunity (7). However, serum levels of this complement component are equivalent in young, preautoimmune B6, B6.Sle1 and B6.Sle1 Sles1 mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of classical complement pathway factors has been most strongly related with systemic lupus erythematosus (20,21) and other immune complex-mediated diseases (22). C4 deficiency could thus be expected to increase EAMG incidence rather than decreasing it.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the clinical observation that deficiency of the early complement components, particularly of the classical pathways, such as C1q, C4, and C2, is a high-penetrance risk factor for developing systemic lupus erythematosus (SLE) (Walport 2001a(Walport , 2001b. Furthermore, mice deficient in C1q and C4 also developed autoimmune diseases resembling human SLE with characteristic findings such as glomerulonephritis and appearance of high titer autoantibodies (Botto et al 1998;Chen, Koralov, and Kelsoe 2000;Paul et al 2002).…”
Section: Complementmentioning
confidence: 99%